Nutrient Composition and Distance from Point Placement to the Plant Affect Rice Growth - HU, Fengqin; WANG, Huoyan; MOU, Pu; ZHOU, Jianmin (Pedosphere, 2018)
Point placement of urea is an efficient technology to improve urea use efficiency in transplanted rice (Oryza sativa L.), but it is largely unknown how nutrient composition in the point placement and the distance from placement site to the plant influence rice root distribution and growth, nutrient uptake, and rice grain yield. A controlled greenhouse experiment was conducted using both N- and P-deficient soil with point placement of N only or N and P together (N + P) at a distance close to or far from the plant, in comparison to an N-spilt application and a no-N control. Both nutrient composition and distance significantly affected rice root growth. Compared with the N point placement, the N + P point placement led to smaller root length and mass densities, higher specific root length (SRL) around the placement site, smaller root system, higher straw mass and grain yield, and higher N and P uptake. The difference between the N + P and N point placements was greater when close to the plant than when far from the plant. It is suggested that higher SRL around the placement site is essential for improving nutrient uptake and rice grain yield, and simultaneous point placement of N and P has a synergistic effect on rice growth.